Efforts to Improve the Professionalism of Nurses in Hospitals: Scoping Review - Indarningsih Indarningsih; Luky Dwiantoro; Zubaidah Zubaidah (Indonesian Journal of Global Health Research, 2025)
Low professionalism of nurses will decrease patient satisfaction, decrease trust in health services, increase the risk of care errors, and legal litigation. Efforts to improve the professionalism of nurses in hospitals need to be made to overcome these problems The purpose of this study was to identify the factors that influence nurses' professionalism and efforts to improve nurses' professionalism. This method using scoping review. The literature search was conducted systematically through Sciencedirect, Scopus, and Pubmed databases with keywords related to nurse professionalism and hospitals, with a publication time limit of January 2015 to March 2025. Inclusion criteria included quantitative and qualitative studies that addressed efforts to improve nurse professionalism in Asian hospitals in English. We using 10 articles for this review. Data extraction was performed using a matrix that included information on authors, year, country, study design, participants, and findings. A total of 10 articles that met the inclusion criteria were analyzed. The synthesized results show that efforts to improve nurses' professionalism involve various strategies that can be classified into internal (e.g., ethical behavior, self-efficacy, role cognition) and external (e.g., positive work culture, leadership support, CPD, work environment) factors. Organizational support, continuous professional development, and a conducive work environment were identified as key elements in improving nurses' professionalism. In addition, individual factors such as motivation, professional identity, and flexibility also play a significant role. Improving the professionalism of nurses in hospitals requires a multidimensional approach that considers both internal and external factors. Effective strategies involve individual development, strong organizational support, provision of continuing education and training opportunities, and the creation of a positive and supportive work environment. Integration of these efforts is essential to ensure sustained professionalism and improved quality of nursing care.